Value appropriation strategies: linking the resource based view to the property rights theory - Sá, Camila Dias de (2019)
This doctoral dissertation examines alternative appropriation strategies of intellectual property rights (IPRs), developed and adopted by firms. The study argues that the traditional theoretical approach used to address this issue, based on Teece\'s (1986) seminal paper \"Profiting from technological innovation\", is not suitable for non-trivial circumstances, outside the industrial and manufacturing sector and which are ruled by sui generis IPRs. To understand the IPRs appropriation efforts undertaken by firms within these peculiar environments, this study suggests the integration of the Property Rights Theory with the Resource Based View approach to Strategy. It is based on the perspective of Property Rights Economics, particularly on the work of Barzel (1997), who conceptualizes resource as a bundle of attributes for which property rights may be granted. Resting on this definition, which was extended by Foss and Foss (2005, 2006), who argue that the resource owner\'s ability to extract and sustain value depends on whether he holds secure property rights over the relevant attribute, I propose the unbundling of the resource attributes, as a strategy to appropriate value. To test the theoretical propositions, I developed a double case study on the soybean and cottonseed breeding in Brazil. To place the reader in this empirical setting, a chapter explains the organizational, institutional and competitive dimensions of the seed-breeding sector. I carried out the double case study through semi-structured interviews with breeding firms, complemented by some descriptive statistics of official data. The main finding of this dissertation refers to the idea of accessing economic rights to a resource that can be dismembered in few attributes, to which individual property rights are assigned, and then benefit from the superior protection offered by one single relevant attribute. The dissertation ends with some reflections on the implications of this finding, on a general basis and particularly regarding the future of seed breeding in Brazil.